GENERAL CHARACTERISTIC OF ATERNATIVE CERTIFICATION OF TEACHERS IN USA - Пазюра, Н. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article is devoted to the issue of teachers’ training by means of alternative certification. The author presents the general characteristic of this training: its contents are analyzed, firms and methods are revealed. Peculiarities of alternative certification are shown: its direction to the needs of a certain region in which they were organized, shortened term of study (from 1 to 3 years), provision necessary psychological and pedagogical support. The article analyses the requirements to those who wish to get teaching profession in alternative certification as well as to those who provide psychological support and pedagogical training on-the-job. The attention is paid to the role of social partners on organization of this training. The conclusion about the importance of alternative certification of teachers for qualitative and quantitative standards of American education is made